An annotated checklist of Australian Mesozoic tetrapods - Poropat, Stephen; Bell, P.R.; Hart, L.J.; Salisbury, S.W.; Kear, B.P. (2023)
In 2020, the Australasian palaeontological association Australasian Palaeontologists (AAP) joined the Australian government-supported Australian National Species List (auNSL) initiative to compile the first Australian Fossil National Species List (auFNSL) for the region. The goal is to assemble comprehensive systematic data on all vertebrate, invertebrate and plant fossil taxa described to date, and to present the information both within a continuously updated open-access online framework, and as a series of primary reference articles in AAP’s flagship journal Alcheringa. This paper spearheads these auFNSL Alcheringa publications with an annotated checklist of Australian Mesozoic tetrapods. Complete synonymy, type material, source locality, geological age and bibliographical information are provided for 111 species formally named as of 2022. In addition, chronostratigraphically arranged inventories of all documented Australian Mesozoic tetrapod fossil occurrences are presented with illustrations of significant, exceptionally preserved and/or diagnostic specimens. The most diverse order-level clades include temnospondyl amphibians (34 species), saurischian (13 species) and ornithischian (12 species) dinosaurs (excluding ichnotaxa), and plesiosaurian marine reptiles (11 species). However, numerous other groups collectively span the earliest Triassic (earliest Induan) to Late Cretaceous (late Maastrichtian) and incorporate antecedents of modern Australian lineages, such as chelonioid and chelid turtles and monotreme mammals. Although scarce in comparison to records from other continents, Australia’s Mesozoic tetrapod assemblages are globally important because they constitute higher-palaeolatitude faunas that evince terrestrial and marine ecosystem evolution near the ancient South Pole. The pace of research on these assemblages has also accelerated substantially over the last 20 years, and serves to promote fossil geoheritage as an asset for scientific, cultural and economic development. The auFNSL augments the accessibility and utility of these palaeontological resources and provides a foundation for ongoing exploration into Australia’s unique natural history. Stephen F. Poropat [stephenfporopat@gmail.com], Western Australian Organic and Isotope Geochemistry Centre, School of Earth and Planetary Science, Curtin University, Bentley, Western Australia 6102, Australia, and Australian Age of Dinosaurs Museum of Natural History, Lot 1 Dinosaur Drive, Winton, Queensland 4735, Australia; Phil R. Bell [pbell23@une.edu.au], Palaeoscience Research Centre, School of Environmental and Rural Science, University of New England, Armidale, New South Wales 2351, Australia; Lachlan J. Hart [l.hart@unsw.edu.au], Earth and Sustainability Science Research Centre, School of Biological, Earth and Environmental Sciences (BEES), University of New South Wales, Kensington, New South Wales 2052, Australia, and Australian Museum Research Institute, 1 William Street, Sydney, New South Wales 2010, Australia; Steven W. Salisbury [s.salisbury@uq.edu.au] School of Biological Sciences, The University of Queensland, Brisbane, Queensland 4072, Australia; Benjamin P. Kear [benjamin.kear@em.uu.se] The Museum of Evolution, Uppsala University, Norbyvägen 16, Uppsala SE-752 36, Sweden.